Laboratory module design for Biology Students: A Systematic review - Wahyu Kusumawardani; Muzzazinah Muzzazinah; Murni Ramli (JURNAL BIOEDUKATIKA, 2020)
Module design for students laboratory activities plays an important role in the effective implementation of scientific investigation in the laboratory. The purpose of this review is to examine the types, topics, competencies, and approaches to develop laboratory module for biology students. The review of the literature was conducted systematically. Eighteen research articles were selected from 41 articles published within 2009 and 2019. The systematic review followed 5 steps. The research articles were searched using Google Scholar's online database and then traced back from the relevant international and national journals. The articles collected were selected by two reviewers who rated the quality. The results of the analysis showed that the laboratory modules are designed using the following basis: online, research, quantitative skills, inquiry, and traditional. The biology topics focused are Genetics, Ecology, Phylogenetics, Biochemistry, Molecular Biology, Evolution, Biotechnology, and Tissue Culture. The methods used for laboratory module development by Indonesian researchers are 4D, ADDIE, R & D, Dick & Carey, and Borg & Gall, while international researchers generally do not specify the name of the method used. Generally, the need analysis which focuses on the novelty of the developed concept is conducted in the beginning. It continues with module designing, validation, implementation, and response survey from the students as the module users.